Electromyographic and systemic physiological thresholds in single-joint elbow flexion movements - Tilp, M.; Kitzberger, L.; Schappacher-Tilp, G.; Birnbaumer, P.; Hofmann, P. (International Journal of Sports Physiology and Performance, 2022)
Purpose: Reported relationships between electromyographic (EMG) thresholds and systemic thresholds based on lactate, ventilation, or heart rate are contradictory. This might be related to the complexity of the investigated whole-body movements involving many muscles with different activation patterns. Therefore, the aim of the study was to investigate these relationships during an incremental single-joint exercise.